2022
DOI: 10.1177/00034894221098704
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Techniques for Nasal Septal Perforation Repair: A Systematic Review

Abstract: Objectives: Surgical repair of nasal septal perforations (NSPs) is technically challenging. Advantages associated with endoscopic NSP repair (ENSPR) include enhanced visualization and its minimally invasive nature. Purely endoscopic techniques have successful outcomes with low morbidity. This study provides a review of clinical features, surgical techniques, and outcomes in patients who underwent ENSPR. Methods: A systematic review was conducted using PubMed/MEDLINE, Cochrane library, and Embase databases. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Currently, success closure rates exceeding 90% are now commonly reported [3 ▪▪ ], however, there is no standard approach or single technique. The different techniques described include unilateral random pattern flaps, interposition grafts, unilateral pedicle septal local flaps, free mucosal grafts and bilateral random patter flaps [3 ▪▪ ,4,17,18].…”
Section: Brief History and Development Of Septal Perforation Repairmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, success closure rates exceeding 90% are now commonly reported [3 ▪▪ ], however, there is no standard approach or single technique. The different techniques described include unilateral random pattern flaps, interposition grafts, unilateral pedicle septal local flaps, free mucosal grafts and bilateral random patter flaps [3 ▪▪ ,4,17,18].…”
Section: Brief History and Development Of Septal Perforation Repairmentioning
confidence: 99%
“…Currently, success closure rates exceeding 90% are now commonly reported [3 ▪▪ ], however, there is no standard approach or single technique. The different techniques described include unilateral random pattern flaps, interposition grafts, unilateral pedicle septal local flaps, free mucosal grafts and bilateral random patter flaps [3 ▪▪ ,4,17,18]. A systematic review performed in 2007 concluded that each technique had its own advantages and drawbacks, however, the authors were not able to conclude anything categorical because the results reported were rarely statistically significant [18].…”
Section: Brief History and Development Of Septal Perforation Repairmentioning
confidence: 99%
See 3 more Smart Citations